The attainment of Bentley's "Measures of musical abilities" by teachers-in-training using suggestopaedia as an instructional strategy - Garlick, Mervyn (College of Music, 2024)
This investigation was the result of evidence of a lack of musical knowledge and elementary practical skills in the majority of first year teachers-in-training at the Cape Town College of Education. This study sought solutions to that problem by assessing the effectiveness of an alternate teaching strategy, based on Suggestopaedia, to the one presently in use. Improvements in particular aural and practical musical skills achieved by the students were measured by the Bentley 'Measures of Musical Abilities' and an Author-Constructed test. The data was analysed using t-tests and one-way analyses of variance tests. The results showed that the method was significantly effective in certain areas of aural discrimination in music and in certain practical musical skills. In the light of these findings, and of factors affecting music education in schools, recommendations for future directions in music education have been made.